2013
DOI: 10.1002/bit.24973
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a cytokine receptor scaffold utilizing multiple different tyrosine motifs

Abstract: Cells have intracellular signal transduction systems to control cellular fates. Cytokine receptors initiate the intracellular signaling by recruiting specific signaling molecules to a range of tyrosine-containing motifs. To specifically activate a target signaling molecule, we previously designed single-chain Fv/cytokine receptor chimeras incorporating single tyrosine motifs in the intracellular domain, and each chimeric receptor activated the corresponding signaling molecule by oligomeric antigen stimulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Among the receptors, 3G3, which has two STAT3 binding motifs connected with a (G 4 S) 3 linker, can activate STAT3 most efficiently. This result is consistent with our previous study demonstrating that the proximity of two motifs has a propensity to inhibit the phosphorylation of each corresponding signaling molecules because the signaling proteins bind to the receptor competitively (Saka et al, ). Thus, insertion of (G 4 S) 3 linker(s) between tyrosine motifs would be important to minimize competitive binding of signaling proteins to our designed receptor scaffolds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the receptors, 3G3, which has two STAT3 binding motifs connected with a (G 4 S) 3 linker, can activate STAT3 most efficiently. This result is consistent with our previous study demonstrating that the proximity of two motifs has a propensity to inhibit the phosphorylation of each corresponding signaling molecules because the signaling proteins bind to the receptor competitively (Saka et al, ). Thus, insertion of (G 4 S) 3 linker(s) between tyrosine motifs would be important to minimize competitive binding of signaling proteins to our designed receptor scaffolds.…”
Section: Discussionsupporting
confidence: 93%
“…While we focused on the peak activity of STAT3 to show that multiple identical motifs can function simultaneously, it would be an interesting aspect whether the peak activity or cumulative activity correlates with cellular responses, especially those for practically relevant cells. In addition, we successfully activated multiple different signaling pathways by the insertion of two different motifs into the cytoplasmic domain of our chimeric receptors in our previous study (Saka et al, ). Thus, this system can control both signaling patterns and activation levels by ligand stimulation and might control cellular fates efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Using this system, we showed that a complex cytokine signaling network in primary HSCs can be dissected, with singling out of the roles of individual signaling molecules. While single motif-incorporated CRs were used in this study, a strategy to construct CRs with multiple functional motifs has also been established [ 36 ]. Such CRs can activate multiple signaling molecules of interest, thereby permitting dissection of synergistic effects of signaling molecules on HSC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has focused on the activation mechanism of cytokine receptors and reprogramming of cellular signal transduction. Using the Janus kinase (JAK)-binding domain of a type-I cytokine receptor c-Mpl, and the tyrosine motif, which is a sequence around a dozen amino acid residues and recruits specific signaling molecules when phosphorylated, we successfully demonstrated specific activation of the target signaling molecules [14][15][16] . However, JAK, an endogenous tyrosine kinase, has a drawback that it constitutively activates STAT5 in a tyrosine motif-independent manner.…”
mentioning
confidence: 99%